2023
DOI: 10.1007/s11524-023-00723-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Guaranteed Income on Health, Finances, and Agency: Findings from the Stockton Randomized Controlled Trial

Abstract: The purpose of this experiment was to test the effects of a $500 per month guaranteed income for 2 years on health and financial outcomes. A mixed-methods randomized controlled trial in Stockton, CA, USA enrolled 131 individuals to the treatment condition and 200 to control to receive a guaranteed income from February 2019 to January 2021. Quantitative data collection began 3 months prior to allocation at 6-month intervals concluding 6 months after withdrawal of the intervention. Qualitative data collection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Prior research shows that unconditional cast transfers reduce hospitalizations and criminalized activity and improve nutrition, mental health, school attendance and grades, psychological well-being, and the probability of healthy birth weights [ 24 28 ]. More recently, early studies of guaranteed income cash transfers in the USA have shown that cash transfer recipients experienced lower rates of income volatility, food insecurity, and improved mental health, energy, and physical functioning [ 9 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research shows that unconditional cast transfers reduce hospitalizations and criminalized activity and improve nutrition, mental health, school attendance and grades, psychological well-being, and the probability of healthy birth weights [ 24 28 ]. More recently, early studies of guaranteed income cash transfers in the USA have shown that cash transfer recipients experienced lower rates of income volatility, food insecurity, and improved mental health, energy, and physical functioning [ 9 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Providing an unconditional cash transfer directly to youth that is not conditional on programming participation may allow them to address their individual and family needs that facilitate thriving in social spaces tailored to their personal goals, including school, and avoid adverse systems interactions, such as justice and/or child welfare investigation involvement. They could also directly improve outcomes by addressing challenges like unstable housing, lack of food security, limited transportation options, and insufficient funds for healthy recreational activities [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social networks for these individuals were densely populated with others who had high exposure because of residential segregation and overcrowded housing. Premature death of working household members may affect wealth generation and accumulation, exacerbating future family strain 30…”
Section: Economic Inequality and Racial Capitalismmentioning
confidence: 99%
“…Pilot GI programs tested with low-income adults have shown impressive gains in economic security that have impacted markers of health and well-being. For example, the Stockton Economic Empowerment Demonstration (SEED) project, a GI program based in Stockton, California, that gave selected residents $500 per month, increased recipients' fulltime employment and decreased anxiety and depression, after 1 year (31). Past GI experiments have found that adolescents in households that received GI were more likely to continue schooling than non-recipient households (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%